Powstanie i działalność Polskiej Partii Socjalistycznej – dawna Frakcja Rewolucyjna w Łodzi i w okręgu (1928-1939) - Nartonowicz-Kot, Maria (Acta Universitatis Lodziensis. Folia Historica, 1997)
As soon as PPS (Polish Socialist Party) opposed the after-May 1926 government in December 1926, a clear division, between J. Piłsudski’s supporters and these activists who gave priority to party interests over personal feelings, appeard. In consequence of a final conflict between these factions, a new party - Polska Partia Socjalistyczna-dawna Frakcja Rewolucyjna PPSdFR (Polish Socialist Party-Former Revolutionary Fraction), leaded by Rajmund Jaworowski and his political friends, came into existence in the autumn of 1928. The PPSdFR organizational committee in Łódź was established on October 22, 1928 with Stefan Płóciennik as a chairman. Not many the PPS members of Łódź joined PPSdFR at the first stage of the split. The number of party members increased next months, however, permanent discords, being a result of wrong personal policy, caused that PPSdFR never played an important part in political life of Łódź. A similar process occured also in other towns of the district, like Pabianice, Zgierz, Zduńska Wola, Tuszyn, and Ruda Pabianicka. During the ten years of its existence PPSdFR showed poor activity which became manifest just at the opportunity of political campaigns for parliamentary or municipal elections. PPSdFR took also steps to divide class trade unions. At the beginning of 1929 the District Council of Trade Unions v/as established in Łódź and it joined Centrala Zjednoczenia Klasowych Związków Zawodowych CZKZZ (The Centre for the Unity of the Class Trade Unions).